Genetic variants in the tumor Necrosis Factor-Related Apoptosis-Inducing Ligand (TRAIL) do not contribute but Death Receptor (DR4) genes may contribute to susceptibility to head and neck cancer in Pakistani population - Sarwar, R; Mansoor, Q; Farooqi, A A; Shahzad, S; Fayyaz, S; Ismail, M (Cellular and Molecular Biology, 2015)
TRAIL mediated signaling in cancer cells has emerged as one amongst the most deeply studied molecular phenomenon. Recent breakthroughs have shown that overexpression of anti-apoptotic proteins, inactivation of pro-apoptotic proteins, transcriptional downregulation of TRAIL, DR4/DR5, degradation of DR/DR5 are some of the mechanisms which dramatically abrogate TRAIL induced apoptosis in cancer cells. Data obtained through genetic studies has highlighted highly polymorphic nature of DR4 and in accordance with this concept, we investigated the association between Head and Neck Cancer and polymorphisms in TRAIL (1595 C/T) and DR4 (C626G and A1322G) gene. We selected 100 patients with Head and Neck Cancer and 100 healthy, sex and age matched volunteers randomly. C626G and A1322G in DR4 gene were analyzed using Polymerase Change Reaction (PCR) – Restriction Fragment Length Polymorphism (RFLP) and Amplification Refractory Mutation System (ARMS) techniques respectively. For TRAIL gene 1595 C>T genotypes, there was no statistically significant role of homozygous CC or TT in Head and Neck cancer. CC was 58% in patients and 49% in controls. CT was 30% in patients and 43% in controls. TT was 12% in patients and 8% in controls. Allele frequency for C was noted to be 0.73 (patients) and 0.705 (controls), p-value (1). For T, 0.025 (patients) and 0.001(controls), p-value (0.88). The genotyping for DR4 gene 626 C>G polymorphism was done for 100 head and neck cancer patients and 100 age and sex matched healthy controls. All the genotypes for the polymorphism were in Hardy-Weinberg Equilibrium. For DR4626 C>G genotype, CC was 10% in patients and 2% in controls. GC was 63% in patients and 40% in controls. GG was 27% in patients and 58% in controls. Interestingly, in DR4 genotyping, CC was predisposing factor and GG acted as a protective factor. Allele frequency for C was noted to be 0.41 (patients) and 0.22 (controls), p-value (0.81). For G, 0.585 (patients) and 0.78 (controls), p-value (0.867). For the A1322G polymorphism, TT was 23% in patients and 36% in controls with a p-value 0.09 (table 6). CT was statistically significant in patients (45%) and controls (28%), p-value 0.04. CC was non-significant in patients (32%) and controls (36%), p-value 0.62 (table 6). C allele was 0.45% in patients and 0.5% in controls. T allele was 0.54% in patients and 0.5% in controls. Future studies must converge on somatic mutations, epigenetic mutations and expression analysis of TRAIL and DR4 to get a step closer to individualized medicine.